Current use of direct oral anticoagulants for atrial fibrillation in Japan: Findings from the SAKURA AF Registry. Issue 4 (2nd January 2017) - Okumura, Yasuo; Yokoyama, Katsuaki; Matsumoto, Naoya; Tachibana, Eizo; Kuronuma, Keiichiro; Oiwa, Koji; Matsumoto, Michiaki; Kojima, Toshiaki; Hanada, Shoji; Nomoto, Kazumiki; Arima, Ken; Takahashi, Fumiyuki; et al.
Abstract: Background: Large‐scale investigations on the use of oral anticoagulants including direct oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) have not included Japanese patients. Methods: We established the multicenter SAKURA AF Registry to support prospective observational research on the status of anticoagulation treatment, especially with DOAC, for AF in Japan. We enrolled 3266 AF patients treated with warfarin ( n =1577) or any of 4 DOACs ( n =1689) from 63 institutions (2 cardiovascular centers, 13 affiliated hospitals or community hospitals, and 48 private clinics) in the Tokyo area. Results: We conducted our first analysis of the registry data, and although we found equivalent mean age between the DOAC and warfarin users (71.8±9.5 vs. 72.3±9.4 years, p =0.2117), we found a slightly lower risk of stroke (CHADS2 score of 0 or 1 [46.9% vs. 39.4%, p <0.0001]) and significantly better creatinine clearance in DOAC users (70.4±27 vs. 65.6±25.7 mL/min, p <0.0001). Importantly, we documented under‐dosing in 32% of warfarin users and inappropriate‐low‐dosing in 19.7–27.6% of DOAC users. Conclusions: Our initial analysis of the SAKURA AF Registry data clarified the real‐world use of anticoagulants, which includes DOACs and warfarin in Japan. The DOAC users were at a lower risk for stroke than the warfarin users. In 20–30% of DOAC users, the dose was inappropriately reduced.